Highly effective companies in supplier quality surveillance practices: a quantitative analysis. Issue 3 (3rd March 2020) - Alves, Thaís da C. L.; Neuman, Yoshua; Walsh, Kenneth D.; Needy, Kim LaScola; AlMaian, Rufaidah
Abstract: Results presented are part of a larger mixed-mode study on supplier quality practices focusing on the cross-analysis of interviews, focus groups, and a questionnaire, which collected actual data about timing, costs, practices, and non-conformances associated with purchase orders (POs) from Engineering Procure and Construct (EPC) projects for four material types considered relevant to projects built by EPC contractors based in the United States. The present discussion specifically focuses on the analysis of the non-parametric dataset obtained from the POs to investigate a subset of companies labelled as highly effective companies (HECs). This contribution is unique as it used a mixed-mode approach to collect data beyond construction sites and investigate the product/supplier side of construction processes to advance knowledge of how materials can be sent to construction project sites free of defects and rework and indicates practices that contribute to this goal. When compared to other companies in the dataset, HECs engage in more hours of observation in suppliers' facilities, communicate more often with suppliers, put more effort and time in the planning stages of the project, use more practices related to supplier quality surveillance and supplier quality management, and find non-conformances earlier in the project.